A Versatile Thiol‐ene/Sol–Gel Two‐Stage Curing Process Based on a Hyperbranched Polyester with Different Degrees of 10‐Undecenoyl Modification. Issue 4 (6th September 2013) - Flores, Marjorie; Foix, David; Serra, Angels; Ramis, Xavier; Sangermano, Marco
<x xml:space="preserve">Abstract</x> Hybrid thiol‐ene system based on a hyperbranched polyester with different degrees of 10‐undecenoyl modification are prepared via a dual UV‐thermal process. The pristine thiol‐ene formulation shows a high reactivity towards UV curing and the addition of the inorganic precursor to the photocurable formulation does not affect the UV‐curing process. The crosslinked systems show an increase of Tg by increasing the vinyl functionality content in the HBP and a Tg increase is also evidenced in the hybrid system as a function of inorganic precursor content. Morphological investigations show that the inorganic domains generated in situ are homogeneously distributed throughout the polymeric matrix. By varying the 10‐undecenoyl modification in the terminal groups of the HBP, the size of the inorganic domains is tunable and it is possible to decrease the dimension of the silica domains by using the HBP with a higher modification degree.<inline-graphic xlink:href="ark:/27927/pgg55mvwnw0" content-type="mame201300264-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />